Errors in Discourse Marker Usage in Descriptive Texts by SMA Negeri 12 Semarang Students - Nurtilek Kadyrov; Januarius Mujiyanto; Sri Wuli Fitriati (English Education Journal, 2023)
This study delves into the analysis of common errors found in descriptive texts authored by a sample of 32 students, randomly selected from SMA Negeri 12 Semarang. Its primary objective is to identify, categorize, and evaluate errors pertaining to adverbial phrases, conjunctions, prepositional phrases, and discourse markers while assessing their impact on the coherence of the text. Employing a rigorous research methodology encompassing both quantitative and qualitative techniques, this study provides a thorough evaluation of the student's writing abilities. Quantitative analysis of the collected data exposes a spectrum of errors, encompassing discourse marker misuses, sentence structure deficiencies, inaccuracies in prepositional phrases, conjunction errors, and problems with adverbial phrases. Notably, discourse marker errors, including the omission of commas and the repetitive use of words, emerged as the most prevalent issues. These errors have the potential to significantly hinder the clarity and overall flow of the text. The motivation for this study arises from the recognition that students often encounter challenges when it comes to effectively utilizing discourse markers and other grammatical elements in their descriptive writing. These difficulties can adversely impact text coherence and, consequently, the overall quality of the students' compositions. In light of the quantitative findings, this research underscores the critical importance of targeted grammar instruction and consistent writing practice to enhance students' writing skills. Addressing these common errors collaboratively, educators and learners can work towards improving the quality of descriptive texts.